Telemedicine for glaucoma: the state-of-the-art and trends of development - S. Yu. Petrov; T. N. Malishevskaya; E. E. Farikova; O. I. Markelova (Российский офтальмологический журнал, 2023)
Glaucoma is the top leading cause of ophthalmic-related disability in almost all Russian regions. It is a chronic lifelong disease which requires regular monitoring (once a year or more often) in a medical facility. Since the population is aging, the prevalence of glaucoma is steadily increasing, which hampers access to medical care. Advances in telecommunications and diagnostic technologies have given rise to programs of TV glaucoma, which are used to pass the basic glaucoma parameters on to a specialist working remotely for interpretation. The Federal Law No 242-FZ on telemedicine came into force on January 1, 2018, but the COVID-19 pandemic sped up the development of information technologies in medicine in general and telemedicine communication in particular. The review presents the data on TV glaucoma programs which point to their effectiveness and provides practical advice. Potentially, telemedicine can facilitate access to medical care. The analysis of the economic factors shows that remote consulting is more cost-effective than traditional face-to-face examination of the patient. TV glaucoma programs often help detect glaucomatous changes in the ONH, so more patients with suspicion of glaucoma are referred for screening.. Publications focused on the experience in using active programs contribute to their further development and introduction to the public health system, which will eventually facilitate the access to quality medical care for patients with glaucoma.